The γδTCR combines innate immunity with adaptive immunity by utilizing spatially distinct regions for agonist selection and antigen responsiveness. (December 2018) - Melandri, Daisy; Zlatareva, Iva; Chaleil, Raphaël; Dart, Robin; Chancellor, Andrew; Nussbaumer, Oliver; Polyakova, Oxana; Roberts, Natalie; Wesch, Daniela; Kabelitz, Dieter; Irving, Peter; John, Susan; et al.
Abstract T lymphocytes expressing γδ T cell antigen receptors (TCRs) comprise evolutionarily conserved cells with paradoxical features. On the one hand, clonally expanded γδ T cells with unique specificities typify adaptive immunity. Conversely, large compartments of γδTCR+ intraepithelial lymphocytes (γδ IELs) exhibit limited TCR diversity and effect rapid, innate-like tissue surveillance. The development of several γδ IEL compartments depends on epithelial expression of genes encoding butyrophilin-like (Btnl (mouse) or BTNL (human)) members of the B7 superfamily of T cell co-stimulators. Here we found that responsiveness to Btnl or BTNL proteins was mediated by germline-encoded motifs within the cognate TCR variable γ-chains (Vγ chains) of mouse and human γδ IELs. This was in contrast to diverse antigen recognition by clonally restricted complementarity-determining regions CDR1–CDR3 of the same γδTCRs. Hence, the γδTCR intrinsically combines innate immunity and adaptive immunity by using spatially distinct regions to discriminate non-clonal agonist-selecting elements from clone-specific ligands. The broader implications for antigen-receptor biology are considered. Hayday and colleagues show that the responsiveness of mouse and human γδ IELs to Btnl or BTNL proteins is mediated by germline-encoded motifs within the cognate TCR Vγ chains, while Vγ chain motifs generated by somatic gene rearrangement remain available for nominal antigen binding.